1995
DOI: 10.1002/kin.550270505
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of the atmospheric oxidation of tertiary amyl methyl ether

Abstract: Tertiary-amyl methyl ether (TAME) is proposed for use as an additive to increase the oxygen content of gasoline as stipulated in the 1990 Clean Air Amendments. The present experiments have been performed to examine the kinetics and mechanisms of the atmospheric removal of TAME. The kinetics of the reaction of OH with TAME was examined by using a relative rate technique in which photolysis of methyl nitrite or nitrous acid was used as the source of OH. The OH rate constant for TAME and two major products (t-amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 21 publications
10
49
1
Order By: Relevance
“…Previous product studies of ether oxidation in the presence of NO have reported small yields of nitrates (RON02), where these nitrates have been quantified they have yields of the order of 1-3% [21]. The observed 85 % I 1 % yield of tert-butyl acetate shows that the peroxy radicals in Figure 5 react with NO mainly via channel 1Su.…”
Section: Ch3mentioning
confidence: 85%
“…Previous product studies of ether oxidation in the presence of NO have reported small yields of nitrates (RON02), where these nitrates have been quantified they have yields of the order of 1-3% [21]. The observed 85 % I 1 % yield of tert-butyl acetate shows that the peroxy radicals in Figure 5 react with NO mainly via channel 1Su.…”
Section: Ch3mentioning
confidence: 85%
“…This method uses a two step mechanism, the formation of product (MDOH) due to reaction of OH ϩ MM followed by OH ϩ MDOH. This approach, which has been previously described in detail [13,14], yields an expression of the following form:…”
Section: Hexamethyldisiloxane (Mm)mentioning
confidence: 99%
“…While several hydroxyl radical (OH) + oxygenated organic bimolecular rate constants are well known, details pertaining to the OH + oxygenated organic compound reaction mechanisms are limited [12,13]. A few recent studies of the products from OH + oxygenated organic reactions have illustrated the complexity of their gas-phase reaction mechanisms [14][15][16][17][18][19][20]. These investigations are needed to support hydroxyl radical reaction mechanism patterns based on chemical structure reactivity relationships [21].…”
Section: Introductionmentioning
confidence: 99%